The Effectiveness of Catastrophe Bonds in Portfolio Diversification - Mariani, Massimo; Amoruso, Paola (International Journal of Economics and Financial Issues, 2016)
The rapid growth of catastrophe bonds in financial markets is due to increasing environmental disasters and consequent economic losses, barely covered by insurance and reinsurance companies. These securities represent an effective solution, allowing the risk transfer to the capital market. The objective of this paper is to prove real advantages of the investor who operates in this market segment, in terms of portfolio diversification. The present work indeed shows how investing in catastrophe instruments produces actual benefits for investors both in term of diversification and total return. In fact the final results of the quantitative analysis show how efficient cat-bonds are in terms of stability, being characterised by lesser volatility and fairly stable returns. Thus, the risk potentially connected to these bonds wouldn’t be a limiting factor for their development. Particularly the trend of catastrophe bonds highlights how the possible implementation and spreading of these instruments could improve portfolio strategies. Keywords: financial markets, catastrophe bond, portfolio diversification JEL Classifications: G1, G11